The merit of rural point-of-care ultrasound: Carotid pseudoaneurysm case report - Jan C. Thirion; Daniël J. Van Hoving (African Journal of Primary Health Care & Family Medicine)
Introduction: Extracranial carotid artery aneurysms and pseudoaneurysms are rare, comprising less than 4% of all peripheral artery aneurysms. Rural primary health care facilities often face significant challenges because of limited access to formal imaging. Point-of-care ultrasound (PoCUS) has the potential to bridge this gap, accelerating timely diagnosis and management in remote settings.